Psychological resources and mechanisms as characteristics of national identity: theoretical justification and empirical research - Fabrykant, Marharyta S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article covers relations between structural and agency approaches to studies of national identity, drawing on the examples of various theories based on each of these approaches. It shows that structural and agency approaches are related o mechanisms and resources of national identity construction in psychology in a different way than in other social sciences. The plausibility of considering these peculiarities gets revealed by means of the author’s own empirical research on national identity.
Keywords: structural approach; agency approach; national identity; psychological resources; psychological mechanisms